2009
DOI: 10.1002/poc.1505
|View full text |Cite
|
Sign up to set email alerts
|

A DFT study on the (2 + 3) cycloaddition reactions of 2‐nitropropene‐1 with Z‐C, N‐diarylnitrones

Abstract: ski a B3LYP/6-31G * calculations for competing (2 R 3)-cycloaddition pathways for 2-nitropropene-1 (1) to Z-C,N-diarylnitrones (2a-e) suggest a concerted reaction mechanism. However, the results point to the strongly asymmetric nature of transition complexes. Increasing polarity of the reaction environment and presence of electron-donating substituents in the nitrone phenyl rings contribute to the higher asymmetry of these structures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…The reaction pathways of the [2 + 3] cycloadditions were tested using the B3LYP/6‐31g(d) theoretical level . A similar approach was found to be appropriate for a number of nitrone [2 + 3] cycloadditions .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The reaction pathways of the [2 + 3] cycloadditions were tested using the B3LYP/6‐31g(d) theoretical level . A similar approach was found to be appropriate for a number of nitrone [2 + 3] cycloadditions .…”
Section: Resultsmentioning
confidence: 99%
“…Although the chemistry of conjugated nitroalkenes has seen intensive development and is relatively well known with detailed data about the regiochemistry, stereochemistry, kinetics, and mechanisms of the [2 + 3] cycloadditions of conjugated nitropropenes ( 1 , 2 , 3 ) to acyclic di‐substituted and tri‐substituted nitrones and cyclic nitrones to be found in the literature, much less is known about the chemical properties of nitroallyls: there are only two reports in the literature for the [2 + 3] cycloaddition of 3‐nitroprop‐1‐ene ( 4 ) with nitrones. These concern the regiochemistry of the reaction of the nitroalkene 4 with C , C , N ‐triphenylnitrone ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Jasiński et al 49 reported the application of bond development indices I C3ÀC4 and I C5ÀO1 calculated by the relations…”
Section: 345mentioning
confidence: 99%
“…However, in the case of strong electrophilic alkenes or considerable shielding of one of the reaction sites, a stepwise mechanism involving formation of a dipolar intermediate may compete with the concerted mechanism [3,4]. In this regard, in a continuation of a study of the mechanism of (4+2) -electron cycloadditions [5][6][7][8][9][10][11], we investigated the reaction pathways of the [2+3] cycloaddition of 2-nitro-1-propene (1) to (Z)-C,N-diphenylnitrone (2). The formation of four regioisomeric and stereoisomeric diarylnitroisoxazolidines 3-6 is possible in the reaction.…”
mentioning
confidence: 99%